¿Qué perspectivas para la cosmópolis? Reconsiderando el debate sobre el universalismo a través de Giambattista Vico - Ballacci, Giuseppe (Foro Interno, 2006)
This article proposes an interpretation of the work of Giambattista Vico in order to show its relevance for the current debate between liberal universalism and its critics. After a critical reconstruction of its origin at the dawn of Modernity, and having iden- tified rationalism as one of its decisive features, we shall analyse some of the criticisms currently levelled against it by various postmodern authors. The work of Vico and of the traditions from which he drank are found to be a rich source of ideas that may lead us toward a way out of the dead-end that this debate is currently facing.